The Vote18 Polemic and Challenges of its Implementation in Malaysia - Nazaruddin, Mohd Izzuddin; Agus Yusoff, Mohammad (Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2024)
Vote18 in Malaysia aims to extend voting rights to individuals aged 18 and older from the former voting age threshold of 21 years and older. This article discusses the challenges associated with implementing Vote18 in Malaysia, aiming to fill the gaps in the scholarly debates on Vote18 and the obstacles to implementing it in Malaysia. Even though the federal constitutional amendment to implement Vote18 was ratified in 2019, its implementation was delayed by two years, raising the essential question: What is the rationale for its delay? The primary data were collected from interviews with four respondents, comprising current and past ministers who had a pivotal role in revising the federal constitution and implementing Vote18, whereas secondary data were gathered from books, journals, and online newspapers. The findings revealed four obstacles to implementing Vote18 in Malaysia. First, the state constitution or state body laws, including the Election Offenses Act 1954, the Elections (Conduct of Elections) Regulations 1981, and the Registration of Electors Regulations 2002, must be amended before allowing people aged 18 and over to vote or run for office. Second, merging data and information stored by numerous government departments and agencies, such as the National Registration Department (NRD), is labour-intensive and time-consuming. Third, the development of a new voting system and the necessary infrastructure are still ongoing. Finally, the most critical hindrance is the government's lack of political will to ensure the initiative's success. Therefore, it can be concluded that lowering the age restriction is among the key components in reforming the Malaysian electoral system.